Re-Visioning Education in Africa Ubuntu-Inspired Education for Humanity (Springer International Publishing, 2018)
This book presents the case for a conceptual and pragmatic revolution of Africa's formal educational systems. Using the context of Ubuntu-inspired education, the authors explore innovative ways to tackle the challenges faced by governments from the local and national level and beyond. Along the way, the editors and their contributors examine important policy questions to encourage fresh thinking on ways to improve the educational system and, in turn, to buoy the development of the region as a whole. .